2011
DOI: 10.1186/1546-0096-9-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography and color Doppler in juvenile idiopathic arthritis: diagnosis and follow-up of ultrasound-guided steroid injection in the ankle region. A descriptive interventional study

Abstract: BackgroundThe ankle region is frequently involved in juvenile idiopathic arthritis (JIA) but difficult to examine clinically due to its anatomical complexity. The aim of the study was to evaluate the role of ultrasonography (US) of the ankle and midfoot (ankle region) in JIA. Doppler-US detected synovial hypertrophy, effusion and hyperemia and US was used for guidance of steroid injection and to assess treatment efficacy.MethodsForty swollen ankles regions were studied in 30 patients (median age 6.5 years, ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 47 publications
3
72
0
4
Order By: Relevance
“…On follow-up, ultrasound can demonstrate normalization or regression of hyperaemia and synovial hypertrophy. 20,51 Similar findings have been shown when ultrasound is used to follow up disease response to antirheumatic drugs 52 and biologic therapies 53 in adults.…”
Section: Disease Activity Assessment and Comparison With Clinical Asssupporting
confidence: 53%
See 2 more Smart Citations
“…On follow-up, ultrasound can demonstrate normalization or regression of hyperaemia and synovial hypertrophy. 20,51 Similar findings have been shown when ultrasound is used to follow up disease response to antirheumatic drugs 52 and biologic therapies 53 in adults.…”
Section: Disease Activity Assessment and Comparison With Clinical Asssupporting
confidence: 53%
“…20 Shahin et al 43 and others have shown an association with circulating Interleukin 6 (amongst other cytokines) and the amount of joint vascularity demonstrated on PD. Colour and PD techniques can potentially be used in addition to B mode imaging to assess synovitis and thus disease activity.…”
Section: Disease Activity Assessment and Comparison With Clinical Assmentioning
confidence: 96%
See 1 more Smart Citation
“…The lack of predictive value of positive PD signal was unexpected; however, as this ultrasound feature, which is a sign of increased synovial vascularisation, is considered a more reliable indicator of active synovitis than the grayscale technique alone 34–37. As opposed to greyscale abnormalities, this ultrasound feature was not detected in healthy children evaluated in our study and in other investigations 15,33.…”
Section: Discussionmentioning
confidence: 99%
“…Further, US-guided joint injections have improved the accuracy of intraarticular corticosteroid injection (IACI) treatment 8,9 . US is also relatively inexpensive, does not require radiation, is well accepted even by small children, can be viewed at bedside, and enables the physician to view different anatomic locations in the same session 10 .…”
mentioning
confidence: 99%